(untitled) (KULT_online, 2010)
The catalogue of works by Daniel Hopfer (1470–1536) preserved by the Munich collection, as presented by Christof Metzger, is, at last, a catalogue raisonné. The content is much more comprehensive than that of the earlier edition, Hollstein’s German engravings, etchings and woodcuts: ca. 1400–1700. Based on a new-found etching that shows the Battle of Thérouanne (Cat.-no. 72), it is clearly pointed out that about 1494 Daniel Hopfer was the first to use this technique. But this is not the only newly discovered sheet of the Hopfer atelier. Because of a former connection, an album with etchings by Hopfer and his atelier was discovered in a collection in Bologna. This unpublished material is presented for the first time in the current catalogue raisonné.